ERCP - Kozarek, Richard A.; Baron, Todd H.; Carr-Locke, David L. (Elsevier/Saunders, 2013)
Explains what you need to know to effectively and safely practice endoscopic retrograde cholangiopancreatography. In this title, high-quality images, illustrative diagrams, and coverage of the advanced techniques guides you through this complex topic and help you achieve optimal outcomes.